Laparoscopic-assisted gastrectomy versus open gastrectomy for T4a gastric cancer in short-term and long-term outcomes - Hao Xu; Feng-Yuan Li; Dian-Cai Zhang; Li Yang; Ze-Kuan Xu (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: To study thesafety of oncologic short-term and long-term outcomes of laparoscopic-assisted gastrectomy (LAG) performed for T4a stage gastric cancer. Methods: Between January 2009 and December 2014, 86 patients with American Joint Committee on Cancer (AJCC) stage T4a gastric cancer underwent LAG or conventional open gastrectomy (OG). Of these patients, 43 patients underwent LAG and they were compared with patients who underwent OG regarding short-term and long-term outcome. Results: The N stage (P=0.685) did not differ between the LAG and OG groups. Postoperative morbidity occurred in 6 (14.0%) OG and 8 (9.3%) LAG cases and postoperative mortality occurred 2 (4.0%) and 0 (0.0%) cases of OG and LAG, respectively. Recurrence occurred in 6 (14.0%) cases and 4 (9.3%) case in the OG and LAG group, respectively (P=0.077). The mean survival time in the OG group was 53.86 m)and in the LAG was 53.97 m with no significant difference (P=0.295). Conclusion: The LAG is a feasible and safe procedure, and has several advantages over conventional OG.